2018
DOI: 10.1016/j.ifset.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electric fields as a green technology for the extraction of bioactive compounds from thinned peach by-products

Abstract: Thinned fruits are agricultural by-products which nowadays have few economic or environmental benefits. However, previous studies have revealed that these immature fruits have a large amount of antioxidant compounds. The aim of this study was to evaluate whether pulsed electric fields (PEF) might be a suitable green technology for enhancing the extraction of phenols, flavonoids and antioxidant compounds from fresh thinned peaches, thus reducing the use of methanol. Moreover, response surface methodology has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 43 publications
2
53
0
2
Order By: Relevance
“…Permeability can be assessed by centrifugation in dry condition. Comparison and evaluation of the degree of permeability and enhancement of extraction are usually achieved between non-PEF-treated (or control sample) and PEF-treated counterparts [ 88 , 200 ]. Moreover, increasing PEF intensity caused higher permeability and consequently the enhancement of extraction of intracellular compounds [ 201 ].…”
Section: Electrical Force Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Permeability can be assessed by centrifugation in dry condition. Comparison and evaluation of the degree of permeability and enhancement of extraction are usually achieved between non-PEF-treated (or control sample) and PEF-treated counterparts [ 88 , 200 ]. Moreover, increasing PEF intensity caused higher permeability and consequently the enhancement of extraction of intracellular compounds [ 201 ].…”
Section: Electrical Force Methodsmentioning
confidence: 99%
“…El Darra et al found an increase in flavonoid production due to an autoprevention mechanism caused by chemical agents such as oxygen [ 187 ]. On the other hand, PEF treatment is associated with the higher enzymatic oxidation of polyphenolic compounds and the more efficient extraction of flavonoids [ 200 ]. However, the application of PEF can also be detrimental due to changes in density and color of fruit products [ 207 ].…”
Section: Electrical Force Methodsmentioning
confidence: 99%
“…Other studies also showed promising results in PEF-assisted extraction of phenolic acids from different food by-products. In a study dealing with polyphenols extraction from peach by-products, Redondo et al [ 43 ] showed that PEF application resulted in an increase in chlorogenic acid (16.3 mg/100 g), coumaric acid (0.8 mg/100 g), and chlorogenic acid (9.8mg/100 g) compared to the amounts extracted without the application of PEF (4.5, 0.2, and 2.5 and mg/100 g, respectively). Furthermore, Martín-García et al [ 44 ], studying PEF-assisted extraction of polyphenols from brewery by-products, showed improvement in the p-coumaric acid and ferulic acid recovery from brewers spent grain compared with the conventional method.…”
Section: Resultsmentioning
confidence: 99%
“…Com isso, eles deduziram que essa tecnologia associada às condições de armazenamento, como tempo e temperatura, pode ser usada para aumentar o potencial antioxidante das maçãs. Semelhante a esse estudo, Redondo et al (2018) verificaram que o uso dessa tecnologia possibilita o aumento da extração de compostos bioativos de frutos de pêssego, por meio da permeabilidade celular alcançada durante o tratamento.…”
Section: Efeitos Dos Métodos Não Térmicos Nas Propriedades Físico-quíunclassified